Reticular reflex myoclonus: a physiological type of human post-hypoxic myoclonus. Issue 3 (March 1977) - Hallett, M; Chadwick, D; Adam, J; Marsden, C D
Abstract : A patient with post-hypoxic myoclonus, sensitive to therapy with 5-hydroxytryptophan and clonazepam, was subjected to detailed electrophysiological investigation. Brief generalised jerks followed the critical stimulus of muscle stretch. The electroencephalogram showed generalised spikes that were associated with, but not time locked to, the myoclonus. The cranial nerve nuclei were activated upward. Analysis of the findings suggests that the mechanism of the myoclonus is hyperactivity of a reflex mediated in the reticular formation of the medulla oblongata.